2007
DOI: 10.5194/nhess-7-177-2007
|View full text |Cite
|
Sign up to set email alerts
|

Field observations of the 17 July 2006 Tsunami in Java

Abstract: Abstract. The 17 July 2006, a tsunami struck the southern coast of Java, Indonesia, causing over 730 casualties. The triggering earthquake located 225 km off the coast of Pangandaran (9.222° S, 107.320° E), occurred at 15:19 LT (UTC +7) with a 7.7 magnitude on the Richter scale (Harward Center and CEA/DAM). In order to calibrate numerical models and understand the phenomenon, we conducted a 6-weeks field survey in July and August 2006 from Cimerak district in West Java to Gunung Kidul district in Central Java.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 9 publications
5
40
0
7
Order By: Relevance
“…The fact that other teams did not measure water levels of this dimension in this area might argue for an overestimation. Our other levels are in line with the measurements from Lavigne et al (2007) and Tsuji et al (2007). Along the coast in the Pangandaran district the maximum water levels ranged from 3.3 m in the sheltered areas close to the Pangandaran peninsula, to 11.9 m in Pananjung Village (Fig.…”
Section: Ground Profiles Inundation Depths and Flow Velocitiessupporting
confidence: 93%
See 2 more Smart Citations
“…The fact that other teams did not measure water levels of this dimension in this area might argue for an overestimation. Our other levels are in line with the measurements from Lavigne et al (2007) and Tsuji et al (2007). Along the coast in the Pangandaran district the maximum water levels ranged from 3.3 m in the sheltered areas close to the Pangandaran peninsula, to 11.9 m in Pananjung Village (Fig.…”
Section: Ground Profiles Inundation Depths and Flow Velocitiessupporting
confidence: 93%
“…Our other levels are in line with the measurements from Lavigne et al (2007) and Tsuji et al (2007).…”
Section: Ground Profiles Inundation Depths and Flow Velocitiessupporting
confidence: 93%
See 1 more Smart Citation
“…Off Java and the Lesser Sunda Islands, devastating tsunamis were induced by the M w =8.3 Sumba earthquake of 1977, the eastern Java earthquake (M w =7.8) of 1994 and the M w =7.7 Pangandaran earthquake in 2006 (ITDB catalogue 2007). Maximum run-up values of respectively 8 m (Kato and Tsuji 1995), 14 m (Tsuji et al 1995a) and 20 m (Lavigne et al 2007;Fritz et al 2007) have been identified.…”
Section: Introductionmentioning
confidence: 93%
“…The largest were the M w =8.3 Sumba Earthquake of 1977, the East Java Earthquake (M w =7.8) of 1994 and the M w =7.7 Pangandaran Earthquake in 2006 (ITDB catalogue, 2007). Tsunami run-up reached 8 m (Kato and Tsuji, 1995), 14 m (Tsuji et al, 1995a) and 20 m (Lavigne et al, 2007;Fritz et al, 2007), respectively.…”
Section: Tectonic Backgroundmentioning
confidence: 99%